Limnological characterization of the water, algae and mud resources used in Copahue Thermal Complex (Neuquén, Argentina) - Flores Melo, Elizabeth Ximena (2021)
We carried out the physicochemical characterization of extreme environments of acidic geothermal springs of the Copahue Thermal Complex, and isolated and cultivated algae used for therapeutic and medicinal purposes. Ecophysiological aspects, algal photosynthetic responses and potential toxicity of sediments were analysed. At the 15 sampling sites (pH: 2.0-6.7, conductivity: 283-3230 µS/cm, temperature: 22-60°C), 11 Cyanobacteria species of a total of 24 algae were identified. The species richness was low with true inhabitants of highly acidic waters: Cyanidium caldarium, Euglena mutabilis, Chlamydomonas acidophila, Achnanthidium minutissimum, and Eunotia exigua, and cosmopolitan species of thermal springs: Mastigocladus laminosus, Leptolyngbia boryana and Phormidium tergestinum. All the species were well adapted to low light levels (15-55 µmol photon.m-2.s-1), and photosynthetic responses were similar to those in comparable environments. pH and temperature were important factors in algal distribution, and N:P relationship suggests that P is the limiting nutrient for algal growth. Fractions controlling P availability in the muds were those bound to organic matter, and Fe/Al oxyhydroxides. Healing muds have the ability to precipitate metals and would not be toxic. Cadmium and other potentially toxic metals were in very low concentrations and pose no risk for the human use as healing muds and bathing.